Linie Harrisa jako miernik reakcji morfologicznej na warunki życia: interpretacje, kontrowersje, propozycje badawcze - Nowak, Oskar (Polskie Towarzystwo Antropologiczne, 1996)
HARRIS LINES AS A MEASURE OF MORPHOLOGICAL REACTION OF LIFE CONDITIONS: INTERPRETATIONS, CONTROVERSIES AND PERSPECTIVES. The paper presents some conclusions concerning the studies on Harris lines which have been carried out for nearly 70 years. Investigations of this type are particularly important for our knowledge of the morphological changes of human skeleton. The objectives of this study were: (1) to present the history of the studies on Harris lines, (2) to point out the main methodological assumption and limits of interpretation, and (3) to review various aspects with their results of the analysis of this phenomenon in physical anthropology. The paper also suggests new perspectives of research which particularly may answer the question whether there are any metrical, biomechanical and biological differences between individuals with and without Harris lines.
HARRIS LINES AS A MEASURE OF MORPHOLOGICAL REACTION OF LIFE CONDITIONS: INTERPRETATIONS, CONTROVERSIES AND PERSPECTIVES